Sosialisasi dan Pendampingan dalam Pembuatan NIB Melalui OSS di Kelurahan Panjunan Kabupaten Kudus: (Socialization and Assistance in Making NIB Through OSS in Panjunan Village Kudus Regency) - Putri Dewi Anggraeni; Dwi Rahmayani; Safira Galuh Yuniarizki; Ayu Nurus Sa’adah; Moerijanto (Prodi Tadris IPA Biologi UIN Mataram, 2024)
Micro, Small and Medium Enterprises (MSMEs) are one of the trade or investment activities that are well known in Indonesia. Many people, especially business owners or managers, are involved in this type of business. Because many people are identified as MSMEs, new problems also arise. These problems include the large number of business actors who do not yet have a Population Identification Number (NIB). Seeing this problem, KKN students carried out outreach and assistance to business people so they could obtain NIB. This community service activity was carried out in Panjunan Village, Kudus Regency. The methods used in this community service activity are observation and interviews. This activity involves MSME staff so that business actors can better understand NIB. The Online Single Submission website, which is an integrated electronic system from the government, is used to complete the NIB process. The result of this training is that business actors in Panjunan Village are able to obtain NIB without any problems, and everything goes according to plan.